Karakteristik Petani Karet Yang Mempengaruhi Sikapnya Dalam Memilih Pedagang Pengumpul di Desa Koto Rajo Kecamatan Kuantan Hilir Seberang - Hendri Winardo; Fajar Restuhadi; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research was conducted in Kotorajo village, Kuantan Hilir Seberang district. The method of taking sampling use probability sampling technique. The method of data analysis using descriptive analysis, Cartesian diagram analysis, and Rank Spearman correlation analysis and the model of Fishbien multiattribute attitude. The result of this research showed that for the sallling rubber of the farmers droved the rubber in to the seller keeper house with th transportation service. The attribute was paying cash, giving loans, keeping the deal, fast and good in service were the excellent attribute that must be hold by the seller keeper. For the relationship between the farmers level of trust, the characteristics of education correlate manifestly with shrinkage and sorting, the characteristics of productions correlate manifestly with attribute paying in advance directly, and provide the production facilities. The characteristics of income correlate manifestly with attribute paying in advance directly and kinship relation and the characteristics of outcome correlate manifestly with attribute providing the production facilities. On the other hand, for the correlation characteristict with the level of interest, the characteristics of the amount of family insurance correlate manifestly with attribute paying in advance directly and kinship relation and the characteristics of outcome correlate manifestly with attribute the price and paying in advance directly. While, the attitude of the farmers of the traders belongs to neutral category. Key words: fcharacteristics, farmer, attitude, attribute, seller keeper.